2011
DOI: 10.1007/s10529-011-0743-0
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma reesei cellobiohydrolase II is associated with the outer membrane when overexpressed in Escherichia coli

Abstract: Cellulose degradation is essential for the future production of many advanced biofuels. Cellulases from the filamentous fungus Trichoderma reesei are among the most efficient enzymes for the hydrolysis of cellulosic materials. One of the cellulases from T. reesei, cellobiohydrolase II (CBH2), was studied because of its industrial relevance and proven enzymatic activity. Using both crude and rigorous membrane fractionation methods we show that full length T. reesei CBH2 is exclusively localized to the outer mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Moreover, the genes of the components of cellulase had been successfully cloned and expressed in T. reesei to enhance both the cellulase production and its performance in enzymatic hydrolysis of lignocelluloses [4,8,29]. In addition, it was found that T. reesei cbh2 gene could be expressed in E. coli but its product was exclusively localized to the outer membrane of E. coli and unable to be excreted, although E. coli has several advantages over eukaryotic hosts including shorter time scales, a well-developed genetic toolbox, and less complex high-throughput screening through directed evolution [30]. P. pastoris, therefore, is an excellent alternative for producing CBH II or other enzymes with simple composition easy for separation and purification.…”
Section: 3mentioning
confidence: 99%
“…Moreover, the genes of the components of cellulase had been successfully cloned and expressed in T. reesei to enhance both the cellulase production and its performance in enzymatic hydrolysis of lignocelluloses [4,8,29]. In addition, it was found that T. reesei cbh2 gene could be expressed in E. coli but its product was exclusively localized to the outer membrane of E. coli and unable to be excreted, although E. coli has several advantages over eukaryotic hosts including shorter time scales, a well-developed genetic toolbox, and less complex high-throughput screening through directed evolution [30]. P. pastoris, therefore, is an excellent alternative for producing CBH II or other enzymes with simple composition easy for separation and purification.…”
Section: 3mentioning
confidence: 99%
“…The most frequently used bacterial expression host in laboratorial studies is E. coli [ 33 ], due to its well-characterized and easy-to-manipulate genetics, the abundance of commercially-available strains and vectors and its ability to express recombinant genes in high yields of up to 50% of the total protein [ 34 ]. However, attempts at the expression of cellulases in E. coli have encountered numerous problems such as degradation of linker sequences in multi-domain cellulases [ 35 - 37 ], formation of inclusion bodies [ 38 , 39 ], incorrect transportation across the outer membrane [ 40 ] and decreased specific activity of the cellulases [ 41 ] (Table 1 ).…”
Section: Bacterial Expression Systemsmentioning
confidence: 99%
“…Cellobiohydrolases are essential components of the fungal cellulase system that include three major classes of enzymes i.e., β-glucosidases, endoglucanases and CBHs ( Garvey et al, 2013 ; Woon et al, 2016a ). CBHs are particularly important in biomass degradation due to their hydrolytic activities toward crystalline cellulose that is abundant in lignocellulose ( Abdeljabbar, Song & Link, 2012 ). CBHs hydrolyse from the termini of cellulose chains in a processive manner, releasing cellobiose as the major hydrolysis product ( Teeri, 1997 ).…”
Section: Introductionmentioning
confidence: 99%